The post-2015 development agenda for diabetes in sub-Saharan Africa: challenges and future directions - Andre M. N. Renzaho (Taylor & Francis Group, 2015)
Background: Diabetes is one of the non-communicable diseases (NCDs) which is rising significantly across sub-Saharan African (SSA) countries and posing a threat to the social, economic, and cultural fabric of the SSA population. The inclusion of NCDs into the post-2015 development agenda along with the global monitoring framework provides an opportunity to monitor progress of development programmes in developing countries. This paper examines challenges associated with dealing with diabetes within the development agenda in SSA and explores some policy options. Design: This conceptual review draws from a range of works published in Medline and the grey literature to advance the understanding of the post-2015 development agenda and how it relates to NCDs. The paper begins with the burden of diabetes in sub-Sahara Africa and then moves on to examine challenges associated with diabetes prevention, treatment, and management in Africa. It finishes by exploring policy implications. Results: With regards to development programmes on NCDs in the SSA sub-continent, several challenges exist: 1) poor documentation of risk factors, 2) demographic transitions (rapid urbanisation and ageing), 3) the complementary role of traditional healers, 4) tuberculosis and the treatment of the acquired immunodeficiency syndrome as risk factors for diabetes, 5) diabetes in complex emergencies, 6) diabetes as an international development priority and not a policy agenda for many SSA countries, and 7) poorly regulated food and beverage industry. Conclusion: For the post-2015 development agenda for NCDs to have an impact, sufficient investments will be needed to address legislative, technical, human, and fiscal resource constraints through advocacy, accountability, political leadership, and effective public-private partnership. Striking the right balance between competing demands and priorities, policies, and implementation strategies hold the key to an effective response to diabetes in SSA countries.